Does job satisfaction moderate the nexus of employee motivation and productivity? Evidence from Nepalese hospitals - Chalise, Dhan Raj; Sharma, Bhumiswor; Chalise, Mahananda; Timilsina, Jagat; Lekhak, Harshita (Asian Economic and Financial Review, 2025)
Healthcare, as a labor-intensive sector, is intricately linked to employee productivity, which is a key determinant of the organization’s efficiency. Therefore, leveraging the full potential of human resources is a prerequisite for achieving higher standards in healthcare unit productivity and establishing a robust health ecosystem. This paper aims to bridge this gap by analyzing the factors driving Nepalese health professionals’ productivity. Data from 386 hospital staff were analyzed using regression and Structural Equation Modeling - Partial Least Squares (SEM-PLS). The findings highlight the significant role of motivators such as remuneration, job achievement, and the work environment in influencing employee productivity. Notably, the study reveals that job satisfaction is pivotal in moderating the association between job environments and employee productivity. The study’s findings have practical implications for Nepali hospital workers, offering actionable insights into addressing staff-related issues and implementing effective management strategies. By understanding the mechanisms of employee motivation, environment, productivity, and job satisfaction, strategic measures can be taken to enhance health efficiency, foster a positive work environment, improve the climate for employees, and acknowledge their contributions. In addition to being a potential area of future study, this study is invaluable for healthcare authorities, management, staff well-being, and policymakers in promoting efficiency.